Recognition of Expertise and Perceived Influence in Intercultural Collaboration: A Study of Mixed American and Chinese Groups. (29th April 2013) - Yuan, Y. Connie; Bazarova, Natalya N.; Fulk, Janet; Zhang, Zhi‐Xue
Abstract : Building on tenets from transactive memory (TM) theory and expectation states (ES) theory, this study examined how communication styles influenced expertise recognition and perceived influence in intercultural groups of Chinese and American members. Controlling for the impact of actual expertise, we found that confident communication did not affect expertise recognition, but affected perceived influence; task‐oriented communication had significant positive impact on both expertise recognition and perceived influence; and finally, talkativeness and dominance did not predict either expertise recognition or perceived influence. These results highlight the importance of shared ES, which people from different cultures may not develop, in expertise recognition and influence inferred from a group interaction, thus, contributing to understanding the role of culture and communication in TM development .